Pengaruh Amelioran Pada Lahan Pasca Tambang Timah Terhadap Pertumbuhan dan Perkembangan Edamame (Glycine max L.) - Sitti NurulAini; Ratna Santi; Zulkipli Zulkipli (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2019)
Sitti NA, Santi R, Zulkipli Z. 2019. Effect of ameliorant on post tin mine land on growth and development edamame soybean (Glycine max L.). In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang 4-5 September 2019. pp. 236-245. Palembang: Unsri Press.Edamame soybean (Glycine max L) growth and development on post tin mining land can be improves by adding some ameliorant. The aim of this research is to determine the ameliorant effects on edamame growth and generative development in post tin mining land. This research used experimental method with randomized block design (RBD). The treatment consisted of ameliorant factor, there were without ameliorant as control (A0), palm oil solid (A1), cow manure (A2), rice straw (A3) and goat manure (A4). The research conducted on Desember 2018 until March 2019, located on 17th years post tin mining land at Dwi Makmur Village, Merawang Sub-District, Bangka Induk District, Kepulauan Bangka Belitung Province. The result showed that ameliorant can improved post tin mining land pH. As a vegetative phase, palm oil solid showed the best effect on plant height and leaf number. Adding ameliorant can caused early flowering compared with control treatment. Goat manure had best effect on edamame yield, can be seen on pods number and pods weight. Goat manure addition as ameliorant on post tin mining land can improved edamame growth and generative development. Keywords: Bangka Belitung Province, cow manure, goat manure, palm oil solid